2021
DOI: 10.1111/nan.12742
|View full text |Cite
|
Sign up to set email alerts
|

G protein‐coupled receptor kinases are associated with Alzheimer's disease pathology

Abstract: Aim Alzheimer's disease (AD) is characterised by extracellular deposition of amyloid‐β (Aβ) in amyloid plaques and intracellular aggregation and accumulation of hyperphosphorylated tau in neurofibrillary tangles (NFTs). Although several kinases have been identified to contribute to the pathological phosphorylation of tau, kinase‐targeted therapies for AD have not been successful in clinical trials. Critically, the kinases responsible for numerous identified tau phosphorylation sites remain unknown. G protein‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 118 publications
3
9
0
Order By: Relevance
“…In agreement with these data, we observe a decrease in constitutive g-secretase activity and Ab generation in both the GRK3 KO and GRK5 KO cells in comparison with control cells, which suggests that GRK3 and GRK5 activity contributes to increased g-secretase activity and Ab generation. Interestingly, our lab recently determined that both GRK3 and GRK5 are abundantly localized around amyloid plaques in human AD brains (Guimarães et al, 2021). Together, these data support the hypothesis that GRK3 and GRK5 activity may contribute to pathogenic Ab generation while GRK2 activity may act in a protective manner to regulate g-secretase activity.…”
Section: Discussionsupporting
confidence: 59%
“…In agreement with these data, we observe a decrease in constitutive g-secretase activity and Ab generation in both the GRK3 KO and GRK5 KO cells in comparison with control cells, which suggests that GRK3 and GRK5 activity contributes to increased g-secretase activity and Ab generation. Interestingly, our lab recently determined that both GRK3 and GRK5 are abundantly localized around amyloid plaques in human AD brains (Guimarães et al, 2021). Together, these data support the hypothesis that GRK3 and GRK5 activity may contribute to pathogenic Ab generation while GRK2 activity may act in a protective manner to regulate g-secretase activity.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, we also found multiple G protein-related signaling pathways changed in patients' brains in an m6A-related way. The effect of G protein receptor-coupled kinases on AD pathology has been reported [43]. FTO, RBM15, YTHDF2, YTHDF3, YTHDC3, HNRNPC, and HNRNPA2B1 were found to play important roles in different brain regions.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have also indicated that the pattern of expression of the GRKs in neurons is cell type-specific in the human brain in AD subjects. Additionally, an overall positive correlation has been established between GRKs 2, 3, and 6 and soluble tau found in the AD brain ( Guimaraes et al, 2021 ). Furthermore, it has been suggested that these kinases may have direct or indirect involvement in the altered tau solubility, tau phosphorylation, as well as tau aggregation.…”
Section: Neu1 and Alzheimer’s Disease Involvement Of More Than One Ce...mentioning
confidence: 98%
“…However, evidence shows that GRKs are also associated with phosphorylation of non-GPCR proteins to manipulate various other cellular responses besides GPCR-dependent mechanisms. GRKs have also been reported to be involved in the pathological phosphorylation and accumulation of tau and amyloid pathology in AD brains ( Guimaraes et al, 2021 ). Studies have suggested their unique role in the pathological processes involved in AD, and thus, they can be a potential therapeutic target.…”
Section: Neu1 and Alzheimer’s Disease Involvement Of More Than One Ce...mentioning
confidence: 99%